2012
DOI: 10.1016/j.bpj.2012.04.006
|View full text |Cite
|
Sign up to set email alerts
|

Long Lifetime of Hydrogen-Bonded DNA Basepairs by Force Spectroscopy

Abstract: Electron-tunneling data suggest that a noncovalently-bonded complex of three molecules, two recognition molecules that present hydrogen-bond donor and acceptor sites via a carboxamide group, and a DNA base, remains bound for seconds. This is surprising, given that imino-proton exchange rates show that basepairs in a DNA double helix open on millisecond timescales. The long lifetime of the three-molecule complex was confirmed using force spectroscopy, but measurements on DNA basepairs are required to establish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 50 publications
2
16
0
Order By: Relevance
“…This is in agreement with our measurements of the lifetime of similar complexes using atomic force microscopy, where we have observed that the zero-force lifetime of hydrogen-bonded complexes tethered in a nanogap is on the order of seconds. 12, 19 Thus, recognition-tunneling may also provide a tool for slowing DNA transport in a nanopore reader.…”
Section: 0 Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in agreement with our measurements of the lifetime of similar complexes using atomic force microscopy, where we have observed that the zero-force lifetime of hydrogen-bonded complexes tethered in a nanogap is on the order of seconds. 12, 19 Thus, recognition-tunneling may also provide a tool for slowing DNA transport in a nanopore reader.…”
Section: 0 Results and Discussionmentioning
confidence: 99%
“…The off-rates are slow (corresponding to lifetimes of seconds) consistent with AFM measurements of the lifetimes of hydrogen-bonded complexes in a nanogap. 19, 12 This behavior has recently been explained as a consequence of the bond confinement in the gap. 21 The on-rates are fast, probably too fast to be measured with the techniques used here, but certainly consistent with DNA sequencing speeds of many tens of bases per second.…”
Section: 0 Conclusionmentioning
confidence: 92%
“…Similarly, AFM force spectroscopy experiments show that the lifetime of single base-pairs formed via either 2 or 3 H-bonds is B2 and 4 s, respectively 40 . Furthermore, these experiments show that H-bonds exhibit lifetimes larger than 0.1 s even in the presence of 40-60 pN load 40 .…”
Section: Article Nature Communications | Doi: 101038/ncomms4941mentioning
confidence: 92%
“…In order to eliminate hidden multiple unbinding events from visibly indistinguishable single unbinding events, we followed a protocol used for identifying the heterogeneity in chemical bonds or hidden multiple bonds as described previously (Fuhrmann et al, 2012). After eliminating all hidden multiple events, the forces were plotted as a histogram for each retracting velocity with bin width calculated according to a statistical method (Scott, 1979).…”
Section: Single Molecule Dynamic Force Spectroscopy Experimentsmentioning
confidence: 99%